Nonalbuminuric Renal Impairment in Type 2 Diabetic Patients and in the General Population (National Evaluation of the Frequency of Renal Impairment cO-existing with NIDDM [NEFRON] 11) - Thomas, Merlin C. (American Diabetes Association, 2009)
OBJECTIVE: Most diabetic patients with impaired renal function have a urinary albumin excretion rate in the normal range. In these patients, the etiology of renal impairment is unclear, and it is also unclear whether this nonalbumunuric renal impairment is unique to diabetes. RESEARCH DESIGN AND METHODS: In this study, we examined the frequency and predictors of nonalbumunuric renal impairment (estimated glomerular filtration rate [eGFR] <60 ml/min per 1.73 m(2)) in a nationally representative cohort of 3,893 patients with type 2 diabetes and compared our findings with rates observed in the general population from the Australian Diabetes, Obesity and Lifestyle Study (AusDiab) survey (n = 11,247). RESULTS: Of the 23.1% of individuals with type 2 diabetes who had eGFR <60 ml/min per 1.73 m(2) (95% CI 21.8–24.5%), more than half (55%) had a urinary albumin excretion rate that was persistently in the normal range. This rate of renal impairment was predictably higher than that observed in the general population (adjusted odds ratio 1.3, 95% CI 1.1–1.5, P < 0.01) but was solely due to chronic kidney disease associated with albuminuria. In contrast, renal impairment in the absence of albuminuria was less common in those with diabetes than in the general population, independent of sex, ethnicity, and duration of diabetes (0.6, 0.5–0.7, P < 0.001). CONCLUSIONS: Nonalbuminuric renal impairment is not more common in those with diabetes. However, its impact may be more significant. New studies are required to address the pathogenesis, prevention, and treatment of nonalbuminuric renal disease.